1994
DOI: 10.3109/00952999409106779
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Male and Female Intravenous Drug Users' Risk Behaviors for HIV Infection

Abstract: Despite the central role played by female intravenous drug users (IVDUs) in the worsening AIDS statistics of states in the northeastern United States, the relative paucity of research into the HIV risk behaviors--particularly risky needle practices--of female drug injections has left significant gaps in researchers' understanding of how and to what extent such women may differ in their risks from their better-studied male counterparts. This study, derived from a sample of 769 out-of-treatment IVDUs residing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 45 publications
5
37
1
2
Order By: Relevance
“…Previous research supports our finding that women's syringe sharing behavior is frequently embedded in sexual relations (Booth, 1995;Davies et al, 1996;Dwyer et al, 1994;Freeman et al, 1994;Gollub et al, 1998;Latkin et al, 1998;MacRae and Aalto, 2000;Sherman et al, 2001;Tortu et al, 2003). As women have historically assumed positions of deference and care-giving in both drug-using networks and the larger society, it is unsurprising that most female syringe sharers in our study reported injecting after their drug-using partners with the same needle.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous research supports our finding that women's syringe sharing behavior is frequently embedded in sexual relations (Booth, 1995;Davies et al, 1996;Dwyer et al, 1994;Freeman et al, 1994;Gollub et al, 1998;Latkin et al, 1998;MacRae and Aalto, 2000;Sherman et al, 2001;Tortu et al, 2003). As women have historically assumed positions of deference and care-giving in both drug-using networks and the larger society, it is unsurprising that most female syringe sharers in our study reported injecting after their drug-using partners with the same needle.…”
Section: Discussionsupporting
confidence: 86%
“…Injecting drug use is a major route of transmission for HIV in the United States (Centers for Disease Control and Prevention, 2002;Centers for Disease Control and Prevention, 2003), and women who inject drugs are at significant risk of infection (Davis et al, 1998;Freeman et al, 1994;Hader et al, 2001;Prevots et al, 1996). Of the more than 150,000 AIDS cases reported among women nationwide, through December 2002, injecting drug use accounted directly for 39% of cases (Centers for Disease Control and Prevention, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of IDUs in the U.S. indicate that female IDUs were more likely than males to have a sexual partner who also injects (Freeman, Rodriguez, & French, 1994;Gollub, Rey, Obadia, & Moatti, 1998;Latkin et al, 1998;Sherman et al, 2001). Studies from the U.S. and Canada reported that women were often initiated into drug use by male partners, supplied with drugs by their partners and were more likely to be "second on the needle" after their partner had finished injecting himself (Davies, Dominy, Peters, & Richardson, 1996;Dwyer et al, 1994;Gollub et al, 1998;Harvey et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Cette vulnérabilité est principalement liée à leur dépendance financière vis-à-vis des hommes pour se procurer des drogues. Les femmes usagères de drogues sont plus précaires et moins autonomes socialement, leurs ressources consistant plus souvent en prestations sociales [13,14]. Dans la dynamique du couple, le conjoint usager de drogues est souvent le détenteur du produit, l'initiateur aux drogues et à l'injection [15].…”
Section: Des Relations Sexuelles Souvent Contraintesunclassified
“…Cette dépendance au conjoint expose les femmes au risque de partage du maté-riel lié à l'injection en raison de leur manque d'autonomie quant au choix des circonstances de consommation. La temporalité de l'acte d'injection qui succède à l'injection du conjoint en utilisant le même matériel expose les femmes de manière importante aux risques de transmission du VIH et du VHC [14]. Tout au long de leurs trajectoires, ces femmes semblent soumises à la contrainte sexuelle à la fois à l'adolescence puis à l'âge adulte.…”
Section: Des Relations Sexuelles Souvent Contraintesunclassified